Factors affecting unmet healthcare needs of low-income overweight and obese women in Korea: analysis of the Korean National Health and Nutrition Examination Survey 2017 - Ju-Hee Nho; Sook Kyoung Park (Korean Society of Women Health Nursing, 2021)
Purpose The purpose of this study was to explore unmet healthcare needs among low-income overweight and obese women and to identify the factors affecting unmet healthcare needs. Methods The study was a secondary analysis of data from the 2017 Korea National Health and Nutrition Examination Survey. A final sample of 388 out of 8,127 participants was analyzed using complex descriptive statistics, the chi-square test, the independent t-test, and logistic regression. Results The mean age of the participants was 66.51±1.05 years. Unmet healthcare needs were experienced by 19.4% of low-income overweight and obese women. Women with depression, stress, and poor self-reported health status were significantly more likely than their counterparts to experience unmet healthcare needs. Poor self-reported health status was confirmed to be related to unmet health needs in low-income overweight and obese women (odds ratio, 2.65; p=.011). Conclusion The study provides the novel insight that the unmet healthcare needs of low-income overweight and obese women were influenced by self-reported health status. Healthcare providers should make efforts to develop strategies to reduce unmet healthcare needs among low-income overweight and obese women, who constitute a vulnerable population.